Adsorbable and self-supported 3D AgNPs/G@Ni foam as cut-and-paste highly-sensitive SERS substrates for rapid in situ detection of residuum - Xu, Yuanyuan; Yang, Cheng; Wang, Minghong; Pan, Xiaoxiao; Zhang, Chao; Liu, Mei; Xu, ShiCai; Jiang, Shouzheng; Man, Baoyuan (Optics express, 2017)
We have proposed a synthetic approach to produce self-supported and bendable surface-enhanced Raman scattering (SERS)-based 3D chemical sensors with high adsorptivity. Such 3D substrates consist of foam-like graphene macrostructures obtained by template-directed chemical vapour deposition on nickel foams (interconnected 3D scaffold of nickel) and uniform and high-density Ag nanoparticles wrapping around the foam graphene, via seed-mediated in situ growth process. Such 3D AgNPs/G@Ni foam substrates show high-quality SERS performance in terms of Raman signal reproducibility and sensitivity for the analyte, resulting from the high density and homogeneity of "hot spots" on AgNPs/G@Ni foam, multiple cascaded amplication (localized surface plasmon mode and optical standing waves or optical refraction) of incident laser to the 3D foam structures and powerful support from nickel scaffold. Moreover, in virtue of the high adsorptivity and sensitivity of AgNPs/G@Ni foam, the low-concentration crystal violet molecules can be easily traced in the curvilinear fish surface, by simply swabbing the surface to achieve molecules concentration effect in the practical applicability. This work shows promising potential in developing the applications of SERS in the foodstuffs processing and security field.